Music and Music Intervention for Therapeutic Purposes in Patients with Ventilator Support; Gamelan Music Perspective - Suhartini, Suhartini (Department of Nursing, Faculty of Medicine, Diponegoro University, 2011)
Background: Gamelan music is one of folk music for Javanese people. Several research studies testing the effects of music were conducted in Western countries. The music studies for therapeutic purposes used classical music commonly. Even in Indonesia, some researchers may use that music for therapeutic purposes. This concern article explains the perspective music and music intervention as therapeutic purposes, view with Javanese classical music.Objectives: To explore the evidence of music and music intervention for therapeutic purposes and to describe the perspective of gamelan music used in nursing interventionMethods: Using five bibliography databases (MEDLINE, CINAHL, Science Direct, Interscience, and Proquest) were searched from 1999-2010 for original clinical reports or reviews that evaluated the use of complementary therapy for therapeutic intervention in patients with ventilator support. The term of complementary therapy, anxiety, and pain were used in a comprehensive search of electronic databases. Articles were screened and excluded based on the title and abstract information.Results: Music brings about helpful changes in the emotional and physical health of patients, and has the ability to provide an altered state of physical arousal and subsequent mood improvement by processing a progression of musical notes of varying tone, rhythm, and instrumentation for a pleasing effect.Conclusion: Music can be used for therapeutic purposes, for instance to reduce anxiety, to decrease pain sensation, and some effects of psychological impact. Include, the gamelan music can be offer for patients for Javanese people in Indonesia.Key words: Music, music intervention, therapeutic purposes